Ecological and geochemical assessment of alluvial soils in the medial Dniester area - Tamara Leah (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The alluvial soils are characterized by a very large variation in the physical, chemical and geochemical properties as a result of the different pedogenesis conditions, the zonal climate, the origin of the river deposits, their texture and composition, the depth and mineralization of the groundwater. The main characteristic of the heavy metal content in the arable alluvial soil profile is the relatively high content of the total and mobile forms in the humiferous horizon (0-23 cm) due to their biogenic accumulation. On the other hand, although a stratification of the alluvial soil profile persists, there is a general pattern of heavy metal distribution reflected by reduction of Mn, Cu, Pb, Ni, an increase Zn, Co, Cr, Cd and Fe content - from top to bottom of profile, with 3 accumulation maxima: biogenic, gleyic and carbonatic barriers. The typical arable alluvial soils are not polluted with heavy metals: their concentration in the soil does not exceed the maximum admissible limits for soils of Moldova.
Keywords: Q2; Q24; 330; Alluvial soil; Biogeochemical barrier; Heavy metals; Lower Dniester